Final Report, 16 Days Campaign, Macedonia
Video Files: Press Conference, Hotel “Holiday Inn”, Skopje, 25.11.2003; TV KISS - Tetovo, 23.11.2003; RTV Prilep - Prilep, 26.11.2003; TV Shtip - Shtip (TV Star), 27.11.2003; Radio' Cherenja' - Shtip, 27.11.2003; Radio - Sv. Nikole, Sv. Nikole, 03.12.2003; RTV - Kocani, Kocani, 05.12.2003; Silent Witness Action, Skopje, 10.12.2003; Silent Witness Action, TV Shutel, Skopje, 10.12.2003; RTV Kumanovo, Kumanovo, 15.12.2003; Macedonian Radio, Radio – Skopje, Telephone Interview, Slides, 16.12.2003; MTV - Skopje Roma Program, 19.12.2003; Conference, Street Action, Television Program, Radio Program.